Rapid propagation of Chrysanthemum indicum L. by meristem culture - Dieu Phuong, Nguyen Thi; Nhut, Duong Tan (Academia Journal of Biology, 2015)
Rapid propagation of Chrysanthemum indicum L. by meristem culture